Predictors of Elbow Torque Among Youth and Adolescent Baseball Pitchers. Issue 9 (July 2018) - Okoroha, Kelechi R.; Lizzio, Vincent A.; Meta, Fabien; Ahmad, Christopher S.; Moutzouros, Vasilios; Makhni, Eric C.
Background: There has been an increasing incidence of overuse elbow injuries among youth and adolescent pitchers. Pitch type has been implicated as a risk factor for excess torque at the medial elbow; however, this has not been definitively demonstrated. Purpose: To assess predictors of torque across the medial elbow in youth and adolescent pitchers with a mobile sensor. In addition, the authors aimed to determine the differences in elbow torque produced according to pitch type (fastball, curveball, changeup) and pitcher demographics. Study Design: Descriptive laboratory study. Methods: Twenty youth and adolescent pitchers were instructed to throw 8 fastballs, 8 curveballs, and 8 changeups in a standardized but randomized sequence over a 25-minute period. Five pitchers were evaluated each day. A sensor placed at the medial elbow reported elbow torque, arm speed, arm slot, and shoulder rotation for each pitch, while a radar gun measured peak ball velocity. The primary outcome was a determination of thrower and pitch characteristics associated with elevated torque across the medial elbow. Secondary outcomes included the evaluation of differences in throwing biomechanics among different pitch types. Outcomes were assessed via a multivariable model, which controlled for possible covariates. Results: In total, 20 youth baseball pitchers with a mean age of 14.1 years (range, 12-17 years) were included in the study. On average, fastballs caused the greatest torque across the medial elbow (least squares mean ± SE, 47.3 ± 0.5 N·m) as compared with changeups (44.2 ± 0.5 N·m; P < .001) and curveballs (45.0 ± 0.5 N·m; P = .002). However, curveballs produced the greatest arm speed (917.8 rpm). Pitchers who started throwing curveballs at an older age experienced less elbow torque ( P < .001). A multivariable model demonstrated that increased ball velocity and body mass index and decreased arm slot were independent predictors of increased elbow torque. Conversely, increasing age, longer arm length, and greater elbow circumference were independent protectors against elbow torque. Conclusion: This study found that among youth and adolescent pitchers, fastballs generate the highest elbow torque while curveballs generated the greatest arm speed. Increased ball velocity and body mass index and decreased arm slot were predictors of elbow torque; however, increasing age and size of a pitcher's arm were protectors against elbow torque. These findings are important to better understand risk factors for overuse injury in this at-risk athletic population. Clinical Relevance: These findings may inform future pitching recommendations with intentions of curtailing medial elbow injuries experienced by young pitchers, such as ulnar collateral ligament injuries.